2015
DOI: 10.1039/c5tb00732a
|View full text |Cite
|
Sign up to set email alerts
|

Star-shaped poly(2-methyl-2-oxazoline)-based films: rapid preparation and effects of polymer architecture on antifouling properties

Abstract: Star-shaped poly(2-methyl-2-oxazoline)-based films prepared through polydopamine-assistance provided enhanced antifouling properties than the linear ones, and showed superior stability than PEG films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 61 publications
0
27
0
Order By: Relevance
“…The degradation of PEG in several oxidative environments, such as in the presence of reactive oxygen species and other biologically relevant conditions that include pH, UV, and cell culture medium, has been studied extensively . Poly(2‐oxazoline)’s derivatives including poly(2‐methyl‐2‐oxazoline) (PMOXA) and poly(2‐ethyl‐2‐oxazoline) (PEOXA) are emerging as alternatives to the widely applied PEG coatings. One of the authors has conducted a few systematic comparative studies between PMOXA‐ and PEG‐based polymer brushes and showed that the higher stability of PMOXA to antifouling properties, in comparison to PEG brushes, is most likely due to the peptidomimetic structure along the PMOXA backbone.…”
Section: Introductionmentioning
confidence: 99%
“…The degradation of PEG in several oxidative environments, such as in the presence of reactive oxygen species and other biologically relevant conditions that include pH, UV, and cell culture medium, has been studied extensively . Poly(2‐oxazoline)’s derivatives including poly(2‐methyl‐2‐oxazoline) (PMOXA) and poly(2‐ethyl‐2‐oxazoline) (PEOXA) are emerging as alternatives to the widely applied PEG coatings. One of the authors has conducted a few systematic comparative studies between PMOXA‐ and PEG‐based polymer brushes and showed that the higher stability of PMOXA to antifouling properties, in comparison to PEG brushes, is most likely due to the peptidomimetic structure along the PMOXA backbone.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure S5(a) (Supporting Information), the N 1s high‐resolution scan of PDA coating can be curve fitted into two peaks with CN (N, N) and ammonium salt/CNH 3 + . After grafting PMOXA chains to the PDA coating further, an additional peak NCO (~400.17 eV) appeared [Figure S5(b), Supporting Information], meaning that PMOXA was grafted to PDA‐modified surface successfully . While grafting PAA‐SH to the PDA/PMOXA‐coated surface further, an obvious peak (S 2p) at 166.4 eV appears as shown in Figure S4 (Supporting Information); meanwhile, the peak area of NCO decreased when PAA being grafted to the PDA/PMOXA‐coated surface which means PAA chains were grafted successfully [Figure S5(c), Supporting Information].…”
Section: Resultsmentioning
confidence: 99%
“…In order to get a detailed view of the film surface composition ulteriorly, the XPS high‐resolution C 1s scans of mixed brushes were also studied (Figure S6, Supporting Information). The C 1s core‐level spectra are curve fitted into five peak components with binding energy at about 284.79, 285.2, 285.95, 287.99, and 288.8 eV attributable to CC/CH, CCOOH, CN/CO, CO, and COOH, respectively . The XPS‐derived percentage content of COOH (Table ) increased with increasing the concentration of PAA‐SH solution used for the preparation of mixed brushes coating.…”
Section: Resultsmentioning
confidence: 99%
“…Entrapment : Polycatecholamine coating can also be physically modified by incorporation of other materials while undergoing polymerization. This can entrap materials within the coating that may not contain the reactive groups necessary for covalent attachment (e.g., polyethylene glycol, polyvinylalcohol, hyaluronic acid, polyacrylamide, heparin, polyzwitterions, poly( N ‐isopropylacrylamide), other hydrophilic functional materials, and antibacterial compounds). Polydopamine and norepinephrine‐based coatings have also been used to physically entrap both small molecules and proteins during formation.…”
Section: Catecholamine Polymers: Chemistry and Structurementioning
confidence: 99%
“…Following this approach, polydopamine and other catecholamines have been modified with various fouling resistant materials and antimicrobial compounds to prevent biofouling of the surfaces . These include hydrophilic antifouling polymers, zwitterionic amino acids, bioinspired antimicrobial compounds, lysing and disinfecting agents, silver nanoparticles, combinations of silver nanoparticles and antifouling polymers, bactericidal enzymes, and the attachment of multidrug eluting polyelectrolyte multilayer coatings …”
Section: Applications Of Catecholamine Polymersmentioning
confidence: 99%